New Online Shunt Acidification for Water Injection Increasing Technology and Its Application in Huanjiang Oilfield - Zhiying Deng; Zhenning Ji; Suiwang Zhang; Lingpu He; Xiaobing Lu; Wenchao Wu; Liwei Xiong; Haiming Fan (Journal of Chemistry)
The poor physical property and strong heterogeneity of Triassic Yanchang formation in Huanjiang oilfield of Ordos Basin are the main reasons for uneven water absorption, partial injection wells underinjection at high pressure, and decline of production. Previously, large numbers of conventional acidifications were used for plugging removal in the reservoir, but the effect was not so good and effective period was short. Aiming at the geological characteristics of Huanjiang oilfield, an online shunt acidification and augmented injection technology which does not stop water injection, pull original production strings out, and continuously inject acid and diverting agent has been proposed. A chelating acid COA-1S with low corrosion rate (0.3675 g/(m2·h)), good retardation capacity (hydrolysis constant = 1.2 × 10−6), and effective chelating ability (precipitation inhibition rate >95%) has been developed, as well as a diverting agent COA-1P with good dispersion in acid solution, diversion effect, and particle size (10–100 μm), which behaves well in COA-1S acid. It has been proved that the online acid system has a good diversion acidizing ability and plugging removal performance in a deep area in the laboratory core physical simulation test. The field test results show that the online shunt acidizing and augmented injection technology could reduce the injection pressure significantly (4.2 MPa) and increase water injection by 10 m3/d for the measured well (H5) and improve the water injection profile prominently. The online shunting acidification and augmented injection technology have the following advantages: simple procedures, fewer equipment needed, high efficiency of depressurization, and increasing water injection, which could effectively improve the profile of water wells, and there is a bright future of the technology.